2018
DOI: 10.1029/2018jd028350
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Regional Mercury Deposition and Emission Outflow in Mainland China

Abstract: Mainland China is the largest emission region of anthropogenic mercury (Hg) in the world. There have been concerns regarding the emission outflow and chemical transport budget of Hg in the region. Earlier assessments of Hg chemical transport were based on relatively outdated emission data. Recent estimates for anthropogenic (Wu et al., 2016, https://doi.org/10.1021/acs.est.6b04308) and natural Hg emissions (X. Wang, Lin, et al., 2016, https://doi.org/10.5194/acp-16-11125-2016) show substantial differences from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 148 publications
(410 reference statements)
2
22
0
Order By: Relevance
“…As mentioned before, during the cold season, air masses that carry some air pollutants from the Asian continent are transported to our monitoring site by westerlies and northwestern monsoons. In the East Asian region, China is one of the major contributors of atmospheric Hg emissions [57], although the estimated emission amounts [58] and emission outflow [59] have been reported to have slightly decreased due to emission controls in recent years. In addition, the Hg emissions in East Asia slightly increased in the period between 2010 (901.4 Mg) and 2015 (1012.3 Mg), although its growth rate has slowed in recent years [60].…”
Section: Long-term Trends Of Atmospheric Gem Gom and Pbm25 Concentrationsmentioning
confidence: 99%
“…As mentioned before, during the cold season, air masses that carry some air pollutants from the Asian continent are transported to our monitoring site by westerlies and northwestern monsoons. In the East Asian region, China is one of the major contributors of atmospheric Hg emissions [57], although the estimated emission amounts [58] and emission outflow [59] have been reported to have slightly decreased due to emission controls in recent years. In addition, the Hg emissions in East Asia slightly increased in the period between 2010 (901.4 Mg) and 2015 (1012.3 Mg), although its growth rate has slowed in recent years [60].…”
Section: Long-term Trends Of Atmospheric Gem Gom and Pbm25 Concentrationsmentioning
confidence: 99%
“…Recent global Hg models estimate that 3600 Mg yr −1 of atmospheric Hg is deposited to terrestrial surfaces, with 1000 Mg yr −1 being re-emitted back to the atmosphere (Outridge et al, 2018). Moreover, compared to primary anthropogenic emissions of Hg (2500 Mg yr −1 ), estimates of re-emissions from soil surfaces are highly uncertain (Outridge et al, 2018;Wang et al, 2018). Compiling data from 132 studies, Agnan et al (2016) found that the Earth's surface (particularly in East Asia) is an increasingly important source of TGM emissions, with up to half of the global emissions derived from natural sources.…”
Section: Introductionmentioning
confidence: 99%
“…The annual loading of total mercury (THg) to subtropical forests in China has been shown to be much higher than forest catchments in Europe and North America (Wright et al, 2016;Zhou et al, 2020a). High Hg deposition has resulted in elevated soil Hg pools in Chinese subtropical forests (Wang et al, 2018;Wang et al, 2009). In contrast, a recent study showed that the Hg deposition and soil Hg concentrations at a temperate forest in China were similar to those in Europe and North America (Zhou et al, 2020a).…”
Section: Introductionmentioning
confidence: 99%
“…Recent global Hg models estimate that 3600 Mg yr −1 of atmospheric Hg is deposited to terrestrial surfaces, with 1000 Mg yr −1 reemitted back to the atmosphere (Outridge et al, 2018). Additionally, compared to anthropogenic emissions of Hg (2500 Mg yr −1 ), estimates of re-emissions from soil surfaces are highly uncertain (Agnan et al, 2016;Outridge et al, 2018;Wang et al, 2018). Compiling data from 132 studies, Agnan et al (2016) found that the Earth's surface (particularly in East Asia) is an increasingly important source of total gaseous Hg (TGM) emissions, contributing up to half of the global emissions from natural sources.…”
Section: Introductionmentioning
confidence: 99%
“…Forests experience highly elevated Hg loads, especially in China (Fu et al, 2015;Wang et al, 2016). The annual loading of THg to subtropical forests in China have been shown to be much higher than some forest catchments in Europe and North America (Wright et al, 2016;Larssen et al, 2008) and high Hg deposition has resulted elevated the soil Hg pools in Chinese subtropical forests (Wang et al, 2018;Wang et al, 2009). However, recent studies showed that the Hg deposition and soil Hg concentration in temperate forest were similar to those in Europe and North America (Zhou et al, 2020).…”
Section: Introductionmentioning
confidence: 99%